2021
DOI: 10.1037/met0000293
|View full text |Cite
|
Sign up to set email alerts
|

A partially confirmatory approach to scale development with the Bayesian Lasso.

Abstract: The exploratory and confirmatory approaches of factor analysis lie on two ends of a continuum of substantive input for scale development. Recent advancements in Bayesian regularization methods enable more flexibility in covering a wide range of the substantive continuum. Based on the Bayesian Lasso (least absolute shrinkage and selection operator) methods for the regression model and covariance matrix, this research proposes a partially confirmatory approach to address the loading and residual structures at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…To achieve a better balance between parameter selection and estimation, research on alternative priors has been developed. J. Chen et al (2021) proposed a one-step analysis using Bayesian lasso and found that lasso outperformed ridge in reducing the bias of estimates and controlling false positive rates in CFA.…”
Section: Regularization In Semmentioning
confidence: 99%
See 4 more Smart Citations
“…To achieve a better balance between parameter selection and estimation, research on alternative priors has been developed. J. Chen et al (2021) proposed a one-step analysis using Bayesian lasso and found that lasso outperformed ridge in reducing the bias of estimates and controlling false positive rates in CFA.…”
Section: Regularization In Semmentioning
confidence: 99%
“…Muthén & Muthén, 1998–2017). Other penalty priors are more challenging to implement but have been demonstrated in a few studies to offer an improved balance between variable selection and model estimation (e.g., Brown & Griffin, 2010; J. Chen et al, 2021; Lu et al, 2016).…”
Section: Mimic Modelmentioning
confidence: 99%
See 3 more Smart Citations